2015
DOI: 10.1111/tsq.12079
|View full text |Cite
|
Sign up to set email alerts
|

Unsettling Standards: The Biological Age Controversy

Abstract: One key debate within the sociology of aging and the life course over the past decade has been focused on understanding the extent to which there has been a shift from a reliance on chronological age to segment the life course and ascertain age‐specific norms, values, and expectations toward a destandardized life course in advanced economies. In this, little attention has been devoted to the infrastructural processes that would support such a transition: the technologies, standards, and conventions that would,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…A number of molecular markers have been used to study the ageing process and to compare chronological age with the predicted age, also termed biological age. The definition of biological age has been a matter of debate for decades 29 as have the biomarkers used to define it 30 . We have shown that the plasma protein abundance profile is highly predictive of both chronological age and basic anthropometrical traits.…”
Section: Discussionmentioning
confidence: 99%
“…A number of molecular markers have been used to study the ageing process and to compare chronological age with the predicted age, also termed biological age. The definition of biological age has been a matter of debate for decades 29 as have the biomarkers used to define it 30 . We have shown that the plasma protein abundance profile is highly predictive of both chronological age and basic anthropometrical traits.…”
Section: Discussionmentioning
confidence: 99%
“…Its advocates are therefore generally more concerned with reducing later life morbidity and disability than extending lifespans indefinitely ( Mackey, 2003 ). This healthspan focus deliberately distinguishes contemporary anti-aging technoscience from pseudo-scientific historic efforts to bolster its scientific legitimacy ( Moreira, 2015 ). It also reflects the emergence of societal concerns regarding the continued extension of global life expectancy, and fears that growing populations of older people are spending more time in (economically undesirable) ill-health ( Crimmins, 2015 ).…”
Section: Anti-aging Technosciencementioning
confidence: 99%
“…These individuals are thought to engage in specific lifestyles based on the consumption of products and lifestyles, including cosmetics, pharmaceuticals, vacations, and gym and club membership. The powerful anti‐aging industry, for example, encourages individuals (especially women) to engage technologies and lifestyles to “slow” the physiological signs of aging (Katz & Gish, ; Moreira, ). Such consumption is a means for individuals to maintain the ideals of a youthful mind and body that dominate mass culture (Gullette, 2004; Twigg, ).…”
Section: Cultural Expectationsmentioning
confidence: 99%